On the first patents, key inventions and research manuscripts about glass science & technology. (December 2016) - Nascimento, Marcio Luis Ferreira; Zanotto, Edgar Dutra
Abstract: The objective is to describe the first patents, key inventions and scientific papers related to glass science & technology. According to the literature and the Guinness Book of Records, the first English recorded patent was granted to John Utynam in England in 1449 and a second in 1552. Regarding publications, the first two papers on glass production were published in 1665 in Le Journal des Sçavans in France and the Philosophical Transactions of the Royal Society in England. We illustrate our points using landmarks that cover half a millennia and constitute advancements in modern life that are substantially connected to and dependent on glass technology. Graphical abstract: Highlights: According to the Guinness Book of Records the first patent was for glass in 1449. The second technical patent issued in England was also for window glass, in 1552. The first papers related to glass (lens) manufacture were published in 1665. Glass landmarks cover half a millennia and constitute pillars of human knowledge. Advances in modern science and technology are strongly connected to glass history.